Assessing the marginal cost of reducing greenhouse gas emissions in the English and Welsh water and sewerage industry: A parametric approach. (June 2021) - Sala-Garrido, Ramon; Mocholi-Arce, Manuel; Molinos-Senante, Maria; Maziotis, Alexandros
Abstract: Reducing greenhouse gas (GHG) emissions involves effort from different sectors of the economy, including the water and sewerage industry. This study estimates the marginal cost of curtailing GHG emissions in the water and sewerage industry using stochastic frontier analysis techniques for a sample of ten English and Welsh water and sewerage companies over the 2010–2019 period. Results illustrated that the average marginal cost of reducing GHG emissions was 0.181 £/Kg CO2 equivalent. The marginal cost estimated notably differs across companies and over time. Findings further illustrate the impact of water companies' operating characteristics on the marginal cost of reducing carbon emissions. Highlights: Marginal cost of reducing GHG emissions in the water industry is 0.181 £/Kg CO2 . The cost of reducing GHG emissions is very variable across water companies. Several operational variables impact on the cost of reducing GHG emissions.